A historical flash flood chronology for Britain. Issue 3 (7th May 2021) - Archer, David; Fowler, Hayley
Abstract: The chronology provides a record of flash flood events in Britain based on data collated mainly between 1700 and 2020. The primary purpose of the chronology is to improve the risk assessment of flash floods of given magnitude. It is divided into 18 regions of the country and contains descriptions of nearly 8000 events. It extends a previous chronology covering northern and southwest England which is provided as an online resource in (http://ceg-fepsys.ncl.ac.uk/outputs/ ). Flash floods have had a variety of previous definitions but are here defined in terms of the speed of onset which can apply to both river floods and surface water floods. The chronology for the first time provides a comprehensive list of surface water floods and their recorded impact on cities, towns and villages. It also draws attention to the prevalence of very rapid rates of rise in river level either as 'walls of water', or at a rate likely to endanger life as a result of intense rainfall. Nearly 300 such events have been identified mainly in upland areas of northern England, Wales and Scotland. Practical and theoretical issues with respect to flood risk assessment and warning are discussed. The chronology is available to download and is hosted on https://www.jbatrust.org/how-we-help/publications-resources/rivers-and-coasts/uk-chronology-of-flash-floods-1/